2014
DOI: 10.1159/000366455
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Hypertrophy and Chronic Renal Insufficiency in the Elderly

Abstract: Background: The global population is aging. Cardiovascular disease is the leading cause of death in both men and women older than 65 years. In particular, elderly patients have an increased prevalence of left ventricular hypertrophy (LVH) and chronic kidney disease (CKD), both of which predict increased cardiovascular morbidity and mortality. LVH and CKD frequently coexist in the elderly, and LVH is a powerful predictor of mortality in patients with end-stage renal disease. Key Messages: Several hemodynamic fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 62 publications
1
11
0
3
Order By: Relevance
“…Also, PTH activates kinase C protein in cardiomyocytes, causing an increase in cellular mass. It has been noted that parathyroidectomy can cause a decrease in LV mass, and this finding supports the role of elevated PTH levels in the development of LVH ( 30 ). Patients with chronic kidney disease are exposed to another bone disease before or after developing kidney disease, i.e., osteoporosis, which is a common disease that is characterized by low bone mass and skeletal fragility resulting in an increased risk of fracture ( 31 ).…”
Section: Discussionsupporting
confidence: 70%
“…Also, PTH activates kinase C protein in cardiomyocytes, causing an increase in cellular mass. It has been noted that parathyroidectomy can cause a decrease in LV mass, and this finding supports the role of elevated PTH levels in the development of LVH ( 30 ). Patients with chronic kidney disease are exposed to another bone disease before or after developing kidney disease, i.e., osteoporosis, which is a common disease that is characterized by low bone mass and skeletal fragility resulting in an increased risk of fracture ( 31 ).…”
Section: Discussionsupporting
confidence: 70%
“…It appears that nonatherosclerotic processes, including left ventricular hypertrophy and fibrosis, account for most of the excess cardiovascular risk in uremic patients [13]. Equally, the increased pressure, volume overload, anemia, hypocalcemia, and hyperphosphatemia usually result in compensatory myocardial hypertrophy and fibrosis, making diastolic dysfunction seem to be more common and occur earlier than systolic dysfunction in young uremic patients [14][15][16]. Furthermore, in our previous study, we found that patients with the normal LVEF, although under long-term regular peritoneal dialysis, maintaining well-controlled blood pressure and stable ultrafiltration and adequate total fluid removal, their LV diastolic function deteriorated as the CKD progressed, in contrast to the stable LV systolic function [17].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the increase of pressure and volume overload, early cardiac function damage is mainly due to compensatory hypertrophy of the myocardium in PD patients [6]. At that time, there is no obvious change in cardiac cavity size and systolic function, and it is still within the normal Values are presented as mean ± SD.…”
Section: Discussionmentioning
confidence: 99%